Penilaian Risiko Kesehatan Kerja pada Penggunaan Pestisida dengan Metode (Hirac) di Perkebunan Sawit Sumatera Selatan Indonesia - Maksuk Maksuk (Health Information : Jurnal Penelitian, 2019)
Along with the increase in oil palm plantations, the involvement of the number of workers in this sector also increases as does the contact of workers to various active ingredients of pesticides. This study aims to assess the risks involved in applying pesticides to oil palm plantations. This study is an observational study using the Hazard Identification Risk Assessment Control (HIRAC) method. Risk control is based on the scale of risk through administrative control and use of personal protective equipment according to standards and the provision of a special site for decontamination after pesticide application. Conclusion: the risk identification hazard control method (HIRAC) is one of the methods used to assess the health risks of workers that contribute to the occupational health and safety management system (SMK3), in particular to assess the health risks of workers. Therefore, this method needs to be developed as a method to assess the health risks of workers in the process of applying pesticides to oil palm plantations.